"Democratic and Humanistic/Humane Paideia in the Euro-Cypriot Polity—Prospects for Reconstruction and Modernization": A Biographical Sociological Analysis of a Reform Initiative in a (De-)Globalizing World. Issue 2 (3rd April 2018) - Klerides, Eleftherios
Abstract : In 2004, a reform report entitled "Democratic and Humanistic/ Humane Paideia in the Euro-Cypriot Polity: Prospects for Reconstruction and Modernization" was published by the Ministry of Education and Culture in the Republic of Cyprus. Professor Andreas M. Kazamias is held to have been the driving force behind this initiative, shaping both the form and the contents of the report. The article takes this claim as its point of departure, seeking to validate, modify or reject it by means of a biographical sociological approach that studies the report as an interplay of history, structure (or culture), and biography.